Thuggee - Wagner, K. author. aut Link
XX, 281 p.
Keywords: Based largely on new material, this book examines thuggee as a type of banditry, emerging in a specific socio-economic and geographic context. The British usually described the thugs as fanatic assassins and Kali-worshippers, yet Wagner argues that the history of thuggee need no longer be limited to the study of its representation.